2011
DOI: 10.1063/1.3668092
|View full text |Cite
|
Sign up to set email alerts
|

High-Q optomechanical GaAs nanomembranes

Abstract: We present a simple fabrication method for the realization of suspended GaAs nanomembranes for cavity quantum optomechanics experiments. GaAs nanomembranes with an area of 1.36 mm by 1.91 mm and a thickness of 160 nm are obtained by using a two-step selective wet-etching technique. The frequency noise spectrum reveals several mechanical modes in the kilohertz regime with mechanical Q-factors up to 2,300,000 at room temperature. The measured mechanical mode profiles agree well with a taut rectangular drumhead m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Recent studies on GaAs disks reported Q Â f products between 10 11 and 10 12 in ambient conditions, 8,10 at the forefront of what has been demonstrated so far with GaAs based mechanical systems. [16][17][18] In this Letter we focus on mechanical dissipation and the Q Â f factor in GaAs disks, with an emphasis on clamping losses. By measuring and modeling the mechanical Q of disks of varying pedestal radius, we find that clamping loss is the dominant loss mechanism when these resonators sit on a simple central pedestal and are operated in vacuum at low temperature.…”
mentioning
confidence: 99%
“…Recent studies on GaAs disks reported Q Â f products between 10 11 and 10 12 in ambient conditions, 8,10 at the forefront of what has been demonstrated so far with GaAs based mechanical systems. [16][17][18] In this Letter we focus on mechanical dissipation and the Q Â f factor in GaAs disks, with an emphasis on clamping losses. By measuring and modeling the mechanical Q of disks of varying pedestal radius, we find that clamping loss is the dominant loss mechanism when these resonators sit on a simple central pedestal and are operated in vacuum at low temperature.…”
mentioning
confidence: 99%
“…5,16,18,19,22,23 It has also prevented development of the MMR for more practical applications. In addition, the large mass of MMRs typically 10 À11 -10 À9 kg and low frequency 15,16,[18][19][20] can also reduce their effectiveness in quantum cavity-optomechanical systems as well as limiting their sensitivity in mechanical detectors. 19 To address these drawbacks, a micron-sized MMR with a small effective mass $10 À13 kg operating at radio-frequencies, has been developed from a piezoelectric material which enables all electrical transduction of the mechanical motion.…”
mentioning
confidence: 98%
“…[12][13][14] Recently, membrane-based mechanical resonators (MMRs) have garnered considerable attention as they enable high quality-factors, Qs. [15][16][17][18][19][20][21] In addition, they also have a large surface area compared to beams/cantilevers which not only makes them easier to use in optical architectures, [15][16][17][18][19] but it could also make them more responsive as detectors. 19 Consequently, the MMR has become a crucial element in many cavity-optomechanical systems, and it is also being rapidly developed for sensing applications.…”
mentioning
confidence: 98%
See 2 more Smart Citations